Multi-Analytical Approach to Study Fresh-Cut Apples Vacuum Impregnated with Different Solutions - Silvia Tappi; Elena Velickova; Cinzia Mannozzi; Urszula Tylewicz; Luca Laghi; Pietro Rocculi (Foods, 2022)
The aim of this study was to evaluate the effect of different solutions for vacuum impregnation (VI) of fresh-cut (FC) apples through an innovative multi-analytical approach. In particular, the individual and synergistic effects of ascorbic acid and calcium lactate on the preservation of freshness of FC apples was assessed through color, texture, microscopy, isothermal calorimetry, and time-domain nuclear magnetic resonance (TD-NMR) evaluations. The analysis was performed immediately after VI and after 24 h of refrigerated storage. The obtained results showed a good preservation of color and higher firmness in the impregnated samples. Concerning the metabolic heat production, a decrease following the VI treatment was observed, especially when the combined solution was used for the impregnation. The TD-NMR studies showed higher changes in terms of signal intensity and transversal relaxation time T2 after 24 h of storage, evidencing the meta-stability of the plant material for its dynamic tissue nature, and the dewatering/impregnation processes evolution until the achievement of dynamic equilibrium.